2014
DOI: 10.1177/0020715214527101
|View full text |Cite
|
Sign up to set email alerts
|

Contextual effects on subjective social position: Evidence from European countries

Abstract: This study investigated subjective social position in 21 European countries using data from the social inequality module of the International Social Survey Programme 2009. Subjective social position shows people’s self-location in a social hierarchy. Most studies on subjective social position have typically involved a few countries and neglected the role of national educational and occupational structures. We hypothesise that these characteristics, together with national-level economic factors, modify the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
77
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(84 citation statements)
references
References 47 publications
5
77
0
2
Order By: Relevance
“…Also, given that income can serve as a buffer for the stress individuals face in their lives, low-income individuals in less egalitarian societies should be more stressed and, thus, less healthy, exacerbating the health gradient in less egalitarian countries. Semyonov et al (2013) point to the neo-materialist pathway (Lynch et al, 2000) that is suggested to connect income inequality and average population health. According to this pathway, societies with a high degree of income inequality are also characterized by a country's systematic underinvestment across a wide range of human, physical, and social infrastructures.…”
Section: H2mentioning
confidence: 99%
See 2 more Smart Citations
“…Also, given that income can serve as a buffer for the stress individuals face in their lives, low-income individuals in less egalitarian societies should be more stressed and, thus, less healthy, exacerbating the health gradient in less egalitarian countries. Semyonov et al (2013) point to the neo-materialist pathway (Lynch et al, 2000) that is suggested to connect income inequality and average population health. According to this pathway, societies with a high degree of income inequality are also characterized by a country's systematic underinvestment across a wide range of human, physical, and social infrastructures.…”
Section: H2mentioning
confidence: 99%
“…The relationship between objective and subjective socioeconomic status (SES) is a classic topic within sociology (Evans and Kelley, 2004;Lindemann and Saar, 2014;Marx, 1976) that has recently resurfaced in public health research (Adler, 2013;Nobles et al, 2013;Singh-Manoux et al, 2005;Wolff et al, 2010). While sociological research on the issue long focused on class conflict and the potential for social revolution, public health research has discovered a robust association between subjective SES and a diverse range of health outcomes, usually over and above the influence of objective measures of social status.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beginning in 1987, many include a question asking respondents to place themselves on a ten-point social ladder reflecting their position in society. 9 This question is widely seen as a good measure of subjective social status with adequate test-retest reliability (Operario, Adler and Williams 2004;Evans and Kelley 2004;Lindemann and Saar 2014). It accommodates a diverse set of potential determinants and offers more cross-national comparability and greater independence from political context than alternate measures that ask respondents to express a 'working' or 'middle' class identity (cf.…”
Section: Empirical Analysismentioning
confidence: 99%
“…16 In the preceding estimations, we focused on variation in the absolute level of social status across respondents at a single point in time (namely, the level of social status they report on a ten-point scale), using fixed effects to adjust for variations in the national mean. 17 However, these national means vary considerably across countries and time in response to a wide range of factors, including most notably the aggregate performance of the economy; and, for the purposes of understanding why support for rightwing populism may have risen over time within some sub-groups of the populace, the most relevant factor is how the status of those groups has changed relative to the status of other groups (Lindemann and Saar 2014;Poppitz 2016). Therefore, in this diachronic analysis, we will focus on the relative social status of a group, namely, the distance between the average level of subjective social status reported by members of the group and the mean level of subjective social status within the society as a whole at that point in time.…”
Section: Changes In Status Over Timementioning
confidence: 99%